The Influence of Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Pershare (EPS) on Share Prices at PT. Bank Raya Indonesia Tbk Period 2014-2023 - Asnahwati (PT Katersi Minar Permata, 2025)
The share price is a reflection of the company's value. PT. share price Bank Raya Indonesia Tbk rose drastically during the Covid 19 pandemic in 2020 and 2021 even though its ROE decreased and was even minus. Furthermore, after the pandemic ended, AGRO's share price fell again. DER, ROE, EPS and PT share price. Bank Raya Indonesia Tbk over the last 10 years has experienced fluctuations and tends to decline. This research aims to determine the effect of Debt to Equity Ratio (DER), Return On Equity (ROE) and Earnings Pershare (EPS) simultaneously and partially on the share price of PT. Bank Raya Indonesia Tbk which is listed on the Indonesia Stock Exchange (BEI) for the 2014-2023 period. This research uses a verification method with a quantitative approach. The analysis used is multiple regression analysis with the help of the SPSS version 24 program. Hypothesis testing used is the F test, T test and determination test. The research uses secondary data in the form of financial reports. The population of this research is all financial reports of PT. Bank Raya Indonesia Tbk and the sample is the balance sheet and profit/loss report of PT. Bank Raya Indonesia Tbk 2014-2023. The research found that Debt to Equity Ratio (DER), Return On Equity (ROE) and Earning Pershare (EPS) simultaneously had a significant effect on share prices, while ROE partially had a significant effect on share prices but DER and EPS partially did not have a significant effect on prices Share.